If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-6w + -1v) + -4(4v + -3w) = 0 Reorder the terms: -3(-1v + -6w) + -4(4v + -3w) = 0 (-1v * -3 + -6w * -3) + -4(4v + -3w) = 0 (3v + 18w) + -4(4v + -3w) = 0 3v + 18w + (4v * -4 + -3w * -4) = 0 3v + 18w + (-16v + 12w) = 0 Reorder the terms: 3v + -16v + 18w + 12w = 0 Combine like terms: 3v + -16v = -13v -13v + 18w + 12w = 0 Combine like terms: 18w + 12w = 30w -13v + 30w = 0 Solving -13v + 30w = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-30w' to each side of the equation. -13v + 30w + -30w = 0 + -30w Combine like terms: 30w + -30w = 0 -13v + 0 = 0 + -30w -13v = 0 + -30w Remove the zero: -13v = -30w Divide each side by '-13'. v = 2.307692308w Simplifying v = 2.307692308w
| A^5+8-2a=0 | | x(x+12)=-28 | | 0.36x=(2.52+0.08)x | | 7x+5=x+8 | | (4x)+(2x)=180 | | 0.36x=2.52x+0.08 | | 5/9+11/18= | | -4(6w+u)-3(5u+6)= | | x^2+7x-20=0 | | 8k=8+k+10 | | 26+X=-36 | | 5x-10=5(x-2) | | 3x+27=21 | | 4t+7+t=19 | | 9(W-2)=-12(2W-W) | | -2(-5x+w)-(-4w-3y)= | | 13.5=-3z | | 4(x-2)+7= | | z+31=21 | | 3(5x-8)-4(4x+5)=1 | | -4x-5-2x=-6x+1 | | 3(7x+3)-11(2x+1)=24 | | -5m+14+6m=-5 | | 113=X-17 | | 5x^5=0 | | 2r-13=41 | | 10y^7+28y^6-6y^5= | | 5(4c-1)-5=17c+2 | | 5x+3-2x=3 | | 2x^2+4+5x=0 | | 4(-3+1)=-10(x-4)-14x | | 2x^2=-4-5x |